The Citizen Trust and Engagement in Indonesia Government’s Social Media and Website - Niken Febrina Ernungtyas; Rino Febrianno Boer (Mediator: Jurnal Komunikasi, 2023)
Social media and government websites can be communication tools to encourage participation and interaction between citizens and government institutions. Digital media may lead to citizen trust and citizen engagement toward the government. The purpose of this study is to examine the model of attention to social media, attention to official government websites, perceptions of transparency, public trust, and civic engagement in the Indonesian context. This study used a quantitative approach by conducting a survey (N = 263). Structural Equation Modeling – Partial Least Square (SEM) is used to assess four hypotheses. This study reveals that Attention to Social Media and Attention to Government Websites moderately explain the influence on Perceived Transparency. Moreover, perceived transparency significantly and strongly influences citizen trust and Citizen Engagement is quite stronger explained by the Citizen Trust.